(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This aims to examine the effect of Corporate Social Responsibility (CSR) on the company financial performance. In this study, the company financial performance is measured by Return on Equity (ROE) and Return on Assets (ROA). Corporate Social Responsibility (CSR) as an independent, variable Return on Equity (ROE) and Return on Assets (ROA) as dependent variables. The sample of this study is the oil and gas sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Data were collected by documentary method and literature study. Sample selection using purposive sampling method and obtained 11 companies. This study used multivariate regression analysis to analyze the data. The results show that Corporate Social Responsibility (CSR) has a positive and significant effect on the company financial performance as measured by Return on Assets (ROA) and has a negative effect on Return on Equity (ROE).